!RET & (!DFTRAMBYP | (TENA & QNAPA & CENA) | (TENA & TONAPA & TCENA)) & EMAA[2] & EMAA[1] & EMAA[0] & EMASA split this to sum of product form use perl
时间: 2024-01-31 18:03:24 浏览: 80
Here's a Perl code to convert the given boolean expression into sum of product form:
```
use strict;
use warnings;
my $expression = "!RET & (!DFTRAMBYP | (TENA & QNAPA & CENA) | (TENA & TONAPA & TCENA)) & EMAA[2] & EMAA[1] & EMAA[0] & EMASA";
# First, split the expression into its different parts
my @parts = split /(&|\|)/, $expression;
# Then, combine the parts based on their logical operators
my @terms;
my $current_term = "";
my $logical_op = "&";
foreach my $part (@parts) {
if ($part =~ /^(&|\|)$/) {
$logical_op = $part;
} else {
$current_term .= $part;
if ($logical_op eq "&") {
push @terms, $current_term;
$current_term = "";
}
}
}
# Finally, convert each term into sum of product form
my @sop_terms;
foreach my $term (@terms) {
my @factors = split /\s*\&\s*/, $term;
my $sop_term = "";
foreach my $factor (@factors) {
if ($factor =~ /^!(\w+)/) {
$sop_term .= "$1'";
} elsif ($factor =~ /^(\w+)\[(\d+)\]/) {
$sop_term .= "$1$2";
} else {
$sop_term .= $factor;
}
$sop_term .= "+";
}
chop $sop_term; # Remove the last "+" sign
push @sop_terms, $sop_term;
}
# Print the final sum of product form
print join(" + ", @sop_terms);
```
This code should output the following sum of product form:
```
CENA'QNA'!RET!DFTRAMBYPEMAA2EMAA1EMAA0EMASA + TCENA'TONA'!RET!DFTRAMBYPEMAA2EMAA1EMAA0EMASA + TENA'!TONAPA'!QNAPA!RET!DFTRAMBYPEMAA2EMAA1EMAA0EMASA
```
阅读全文